Maritime accidents analysis using maritime human factors and analysis model - Eslam A. Youssef; Sameh F. El Sayed; Said Abdelkader (Maritime Research and Technology)
The majority of global trade is still carried out by the commercial shipping sector, although it lags behind other transport sectors in terms of safety and accident reduction. Human error is recognized as the most likely cause of maritime accidents.   Received: 13 September 2022 Accepted: 22 October 2022 Published: 27 January 2023